Study on Mechanical Properties of Submunition’s Ribbon Straightening Section - Dong-ze Qin; Wei Zhang; Shu-Yun Zhang; Tian-Ji Guo; Shui-Yuan Pei; Jin-Shi Zhang (International Journal of Aerospace Engineering)
The humanitarian damage caused by the unexploded submunitions is one of the hot issues of concern to the international community at present. A portion of the submunition that did not explode was caused by a break at the connection between the ribbon riveting and the fuze. According to the physical structure of the submunition and the trajectory into which it was ejected, we analyzed the forces of the submunition in flight, deduced the related mathematical models, and clarify the key elements of the mechanics. In this paper, the commercial simulation software was used to calculate the mechanical properties of the ribbon. And the variation regularity between drop velocity and straightening force of ribbon are revealed. And the response characteristics of different material ribbon with different sizes of riveting holes and riveting joints under tensile action were simulated. The simulation results show that, in the trajectory environment with 30 m/s~55 m/s typical stream speed, the tensile force of the ribbon is less than 300 N, and the application concentration of the connecting parts of the riveting joint and the ribbon will not cause the failure of the kevlar ribbon, but it will cause the failure of the nylon ribbon. In order to verify the variation of the tension of kevlar ribbons in different trajectory environments, we designed the experimental scheme of tension test of the ribbon straightening section of submunition and conducted experiments. Experimental results and numerical simulation results revealed the same law. This paper provides effective technical support for solving the problem of unexploded submunitions.